Reproduction,blood and plasma parameters and gill histology of vendace (Coregonus albula L.) in long-term exposure to acidity and aluminum - Vuorinen, Pekka J.; Keinänen, Marja; Peuranen, Seppo; Tigerstedt, Christina (Academic Press, 2003)
Vendace were exposed to pHs 4.75 and 5.25 with or without added aluminum (200 mg=7.4 mmol Al L-1) from late endogenous vitellogenesis in July through the spawning period. At the normal time of spawning,when 48% of the control females had already released their eggs,50% of females at pH 4.75+Al had completely unovulated oocytes. The final proportions of completely ovulated females were 14%,36%,25%, 61%,and 81% at pH 4.75+Al,pH 4.75,pH 5.25+Al,pH 5.25,and in the control group, respectively. Delayed testes regression was seen in males at pH 4.75+Al. A clear decrease in plasma Na+ and Cl- and an increase in blood glucose concentration was detected only near spawning time,from October to November,coincident with Al accumulation inside the gill tissue. It is concluded that seasonal changes,probably related to reproductive physiology or to the decrease in water temperature,are associated with the increase in Al toxicity in vendace.
Keywords: vendace; Coregonus albula L.; plasma chloride; blood clucose; gill histology; Coregonus albula; reproduction; ovulation; chlorides; blood; clucoses; gills; histology; pH; acidity; aluminium